1952
DOI: 10.1161/01.cir.5.5.707
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Bishydroxycoumarin (Dicumarol) in Acute Myocardial Infarction

Abstract: Many physicians find it difficult to decide whether or not a patient sustaining a mild episode of acute myocardial infarction should be treated with anticoagulant drugs. The Committee for the Evaluation of Anticoagulants in the Treatment of Coronary Occlusion with Myocardial Infarction (American Heart Association) has recommended the employment of such therapy in patients with this disease, unless contraindications to anticoagulant therapy exist. Data are presented to show that in "good risk" patients treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1952
1952
1967
1967

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…In those aged 65 or more the mortality from coronary heart disease is high. Russek et al (1951) found it to be 40% in those aged more than 60 and 60% in those who were a poor risk. This increase in mortality in the aged appears to be due to a higher incidence of more severe attacks.…”
Section: Discussionmentioning
confidence: 97%
“…In those aged 65 or more the mortality from coronary heart disease is high. Russek et al (1951) found it to be 40% in those aged more than 60 and 60% in those who were a poor risk. This increase in mortality in the aged appears to be due to a higher incidence of more severe attacks.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years the use of heparin has been advocated for the prevention of recurrent infarction and for the relief of angina pectoris. The favourable effect on angina when administered intermittently twice weekly, as observed by Graham et al (I95I) and Engelberg (1952), could not be confirmed by several workers (Russek et al, 1952;Miller et al, 1952;Binder et al, 1953;Gruner et al, 1953;Rinzler et al, I953; Chandler and Mann, 1953). However, Engelberg et al (i955) administered 200 mg. of heparin by the subcutaneous route twice weekly to o05 survivors of myocardial infarction for a total period of 2,067 patient-months with only four deaths, whereas of 118 control patients receiving placebo treatment, 2z died during a similar period of observation.…”
Section: Coronary Artery Disease Including Myocardial Infarction Andmentioning
confidence: 88%
“…The sublingual route has been found to be most useful clinically (Riseman et al, 1958) ; for when the drug is swallowed, even in greatly increased doses, it is much less effective and the onset of activity is considerably delayed (Russek et al, 1953 ;Russek, 1956). The introduction of aerosol administration of glyceryl trinitrate theoretically offers more rapid absorption through the alveolo-capillary membrane, and enables more rapid access to the myocardium and coronary vessels by eliminating the mouth-to-lung circulation time, usually 10 to 12 seconds.…”
Section: Discussionmentioning
confidence: 99%